SISTEM PENGENDALIAN INTERNAL MASJID BERBASIS NILAI AMANAH, MURAQABAH, DAN UKHUWAH - Risady, Adryan; Abdul Gafur (Forum Dosen Ekonomi dan Bisnis Islam (FORDEBI), 2023)
This research aims to formulate the concept of a mosque's internal control system based on Islamic values. The analytical tool used is transcendental phenomenology, which has developed into Islamic phenomenology. Four Mulawarman University Al-Fatihah mosque administrators were selected as informants. The results showed that the Al-Fatihah Mosque has a strong interactional relationship pattern, like brothers, among its worshipers. The concept of Islamic values of amanah, muraqabah, and ukhuwah is the basis for forming the mosque's internal control system. This research contributes to the development of the concept of Islamic mosque internal control and helps regulators design policies related to mosque management and Islamic internal control. Abstrak Penelitian ini bertujuan untuk merumuskan konsep sistem pengendalian internal masjid berlandaskan nilai Islam. Alat analisis yang digunakan adalah Fenomenologi transendental yang telah berkembang dan menjadi fenomenologi Islam. Empat orang Pengurus masjid Al-Fatihah Universitas Mulawarman dipilih sebagai informan. Hasil penelitian menunjukkan Masjid Al-Fatihah memiliki pola hubungan interaksi yang kuat selayaknya saudara diantara jamaahnya. Konsep nilai Islam amanah, muraqabah, dan ukhuwah menjadi dasar pembentuk sistem pengendalian internal masjid. Penelitian ini berkontribusi dalam pengembangan konsep pengendalian internal masjid bernilai Islam dan membantu regulator dalam merancang kebijakan terkait pengelolaan masjid dan pengendalian internal bernilai Islam.